Exploring how workplace and social policies relate to caregivers' financial strain. Issue 8 (17th November 2018) - Greenfield, Jennifer C.; Hasche, Leslie; Bell, Lauren M.; Johnson, Heidi
ABSTRACT: Informal caregiving is a critical component of the US long-term care system, but can have significant negative impacts on caregiver employment, finances, and well-being. An online survey of Colorado caregivers was piloted in 2016–17 to explore whether workplace and social policies such as access to paid family leave and public health insurance can buffer the negative financial impacts of caregiving and help caregivers to remain in the workforce. Using standardized measures, the survey assessed caregivers' employment and financial status, well-being (physical and mental health, caregiver strain, benefits of caregiving), access to workplace supports, and covariates (e.g., caregiver demographics, health, social support, and service utilization). Ninety-five caregivers, recruited through community agency partners, completed the survey. Respondents were predominately female (89%), middle-aged ( M = 57), non-Hispanic White (64%) or Latino/a (22%), and caring for a parent (40%) or spouse (30%) for over one year. Half (51%) reported working full- or part-time jobs, while 16.4% had stopped working because of caregiving. In multivariate regression modeling, predictors of financial strain included the care recipients' financial strain and the caregiver's reduction or ceasing of work. Medicare may be protective to minimize caregivers' need to reduce or cease work. Implications for caregivers' ability to stay engaged in the workforce and prepare for their own retirement are explored.